Weakly coupled de Sitter vacua with fluxes and the swampland - Daniel Junghans (Journal of High Energy Physics, 2019)
Abstract It was recently argued that the swampland distance conjecture rules out dS vacua at parametrically large field distances. We point out that this conclusion can in principle be avoided in the presence of large fluxes that are not bounded by a tadpole cancellation condition. We then study this possibility in the concrete setting of classical type IIA flux compactifications with (anti-)O6-planes, (anti-)D6-branes and/or KK monopoles and show that, nonetheless, parametrically controlled dS vacua are strongly constrained. In particular, we find that such dS vacua are ruled out at parametrically large volume and/or parametrically small string coupling. We also find obstructions in the general case where the parametrically large field is an arbitrary field combination.